Synthesis, Characterization and Antibacterial Mechanism of Action of (Fluoro) Quinolones: An Overview - Arama, Dominique Patomo; Somboro, Anou Moїse; Dackouo, Blaise (European Journal of Applied Sciences, 2023)
Quinolones are used to treat bacterial infections. Given their good tolerance and demonstrated activity, fluoroquinolones are widely prescribed. This wide use has unfortunately led to bacterial resistance increase. Many efforts have been made to develop new fluoroquinolone antibiotics. However, new and more effective derivatives need to be investigated. This is an overview of studies done these last decades, on fluoroquinolone synthesis, their characterization and their mechanism of actions.